The effects of Lactobacillus reuteri on the inflammation and periodontal tissue repair in rats: A pilot study - Garcia, Valdir Gouveia [UNESP]; Miessi, Daniela Maria Janjácomo [UNESP]; Rocha, Tiago Esgalha da [UNESP]; Gomes, Natália Amanda [UNESP]; Nuernberg, Marta Aparecida Alberton [UNESP]; Cardoso, Jânderson de Medeiros; Ervolino, Edilson [UNESP]; Theodoro, Letícia Helena [UNESP] (Springer Nature, 2022)
Objective: The aim of this study was to evaluate the effects of probiotic (PRO) Lactobacillus reuteri (DSM17938) as an adjuvant to the treatment of experimental periodontitis (EP). Material and methods: Fifty-four male adult Wistar rats were included. EP was induced and maintained for 7 days. Subsequently, the ligature was removed and the animals were allocated into three different experimental groups (n = 18/group): EP – no local treatment, the animals received four systemic saline solution (SS) administrations; SRP+SS, the animals underwent SRP treatment, followed by SS administration; and SRP+PRO, the animals received SRP treatment, followed by the systemic administration of PROs (Lactobacillus reuteri; 0.16 ml/day). Six animals from each group were euthanised at 7, 15 and 30 days. Histological and histometric analyses of alveolar bone loss (BL) and immunohistochemical analyses for TRAP, RANKL, OPG, OCN, and PCNA were performed. Shapiro–Wilk, ANOVA, post-hoc Tukey, Kruskal–Wallis, Student–Newman Keuls were performed. Results: The SRP+PRO group presented a reduction in inflammation. At 15 days, a lower BL was observed in the SRP+SS and SRP+PRO groups. Greater immunolabeling was noticed for PCNA at 15 days in the SRP+PRO group than in the SRP+SS group. The SRP+PRO group demonstrated a higher OCN immunolabeling pattern than the EP group at 15 and 30 days. Conclusion: The use of Lactobacillus reuteri as an adjuvant to SRP for the treatment of EP showed promising results in the control of local inflammatory responses, and enhanced the periodontal tissue repair process according to the employed concentration.
Keywords: Dentistry; Lactobacillus reuteri; Periodontal disease; Periodontology; Probiotic